Pseudo-Cerebrospinal Fluid Rhinorrhea Resulting from Aberrant Cross-Innervation of Trigeminal and Facial Nerves following Skull Base Surgery - Grannan, Benjamin L.; Bi, W. L.; Dunn, Ian F. (Journal of Neurological Surgery Reports, 2015)
Objectives Pseudo-cerebrospinal fluid (CSF) rhinorrhea is a rare phenomenon, presumed to result from aberrant autonomic reinnervation of the paranasal mucosa following injury to the greater superficial petrosal nerve or periarterial plexus. In this report, we discuss the case of a postoperative patient with pseudo-CSF rhinorrhea exacerbated by chewing and propose a novel mechanism of pseudo-CSF rhinorrhea.Case Report A 46-year-old man was found to have mastication-induced unilateral clear rhinorrhea following transtemporal resection of a cerebellopontine angle tumor. Computed tomography cisternogram and β-2 transferrin analysis proved negative for any evidence of CSF leak.Conclusions Pseudo-CSF rhinorrhea exacerbated by mastication has not been previously reported in the literature. We propose aberrant cross-innervation of the trigeminal and facial nerves as the mechanism underlying the patient's condition. Pseudo-CSF rhinorrhea is an important entity to identify following skull base surgery because it may spare patients from the unnecessary invasive procedures and morbidity associated with the management of a presumed CSF leak.
Keywords: nasal hypersecretion; pseudo-cerebrospinal fluid rhinorrhea; trigeminal-facial nerve regeneration